Retirement in Dual‐Career Families: A Structural Model - Gustman, Alan L.; Steinmeier, Thomas L. (Journal of Labor Economics, 2000)
A structural econometric model of retirement of dual-career couples is specified and estimated with panel data from the National Longitudinal Survey of Mature Women. A coincidence of spouses retiring together, despite the younger ages of wives, suggests explicit efforts at coordination. The estimates suggest that one reason is a correlation of tastes for leisure. More important, each spouse, and perhaps husbands in particular, values retirement more once their spouse has retired. The opportunity set accounts for peaks in the retirement hazards of each spouse individually, but not for peaks in the simultaneous retirement of both spouses. Copyright 2000 by University of Chicago Press.